Critical success factors for different organizations in construction projects - Inayat, Asfandyar (Kansas State University, 2012)
Researchers have been compiling lists of key factors the presence or absence of which have determined the success or failure of projects. Early researches of critical success factors were largely theory based; subsequent researches employed the use of statistics and continuously refined methods like neural network and the analytical hierarchy process. Over the passage of time, the focus has narrowed down from broad generalization of ‘projects’ to ‘project classes’. The thesis can be broadly divided into three components. First Component: The first component (Chapter 1, 2, and 3) leads an insight into the basic concept of success factor studies, and the empirical frameworks adopted for identification of critical success factors. The second and the third component, comprises literature review and original research, respectively. These components pertain to success factor studies of construction projects, and are introduced as below. Second Component: The second component (Chapter 4: Review Component) sets out to choose from among a treasure of resources on construction projects, three such state of the art works that can best explain the progress in search of success factors over a period of the foregoing 25 years. After discussing each work in detail, the reader’s attention is drawn to a collective discussion, and summary towards the end of the Review Component. The review includes the following works: (1) Pinto and Covin, 1989, (2) Ashley et al., 1987, and (3) Kog and Loh, 2011. Pinto and Covin (1989) endeavored to set aside the convenient research trend of treating all project types (Manufacturing, R&D, Construction etc.) as similar. It was felt that management practitioners considered the generalized project management prescriptions offered by researchers as mostly inapplicable to the unique situations posed by their respective classes of projects. Stepwise regression analysis was employed to seek separate sets of CSFs for construction and R&D projects. The choice of these two project types was made as they apparently lied on opposite ends of the spectrum of characteristics. The phases of project lifecycle considered for determining CSFs were conceptualization, planning, execution, and termination. It was concluded that though identification of a set of general critical success factors has some benefits for both academics and practitioners, strict adherence to them would not necessarily ensure project success. It was proved that every project type offers its own set of problems, and that these vary over a project’s lifecycle. The review briefly touches upon the work of Ashley et al. (1987) so as to lead an insight into yet another methodology adopted by CSF researchers. This study views project success from the project managers’ perspective for the owner and contractor organizations they works for, and does not take into consideration the view point of other professionals working for owner, contractor and consultant organizations. Hypothesis testing was employed to find those factors that exhibited strong statistical difference while going from average to outstanding projects. Kog and Loh (2011) studied a possible dissimilarity between CSFs pertaining to different components of construction projects: (1) civil works, (2) architectural works, and (3) mechanical and electrical works. Using the Analytical Hierarchy Process the CSFs were compared separately for the objectives of budget, schedule, quality, and overall performance. They concluded that, on the whole, markedly distinct sets of factors were perceived as crucial by professionals associated with these three components. Apart from their varying job descriptions, the divergence in views of professionals was interpreted to be an outcome of the different frames of time that they mostly work in. While a major portion of civil and structural works would be undertaken in early project-life, mechanical and electrical works, and architectural works would be initiated later in the project’s life. For the three components of construction projects (C&S: civil & structural, M&E: mechanical & electrical, and architectural works), the highest correlation of views was seen to exist between the C&S and M&E, while the lowest was always that between the M&E and the architect. This trend remained the same whether the goal of overall performance or any of the three objectives were taken into consideration. Third Component: The thesis terminates with the original work (Research Component: Chapter 5) conducted by the author in the light of Chua et al. (1999) that had attempted, though very briefly, to distinguish between CSFs for different organizations involved in construction projects. Because the survey sample of Chua et al. (1999) was quite small, the researchers referred to their findings regarding organization-based CSFs as inconclusive. It was suggested that further research be conducted in this regard. Addressing these recommendations, the ‘Research Component’ has differentiated the CSFs based on organizational backgrounds of project participants: consultants, contractors, and project management organizations. Spearman’s test on overall rankings of 40 significant factors results in a highest level of correlation between the managers and contractor personnel (rs=0.54), followed by that between the managers and the consultants (rs=0.50), and a least correlation between the contractor personnel and the consultants (rs=0.19). Managers not only maintain a significant presence on the site with the contractors, but also coordinate with the consultants regarding any design-construction issues that arise more than often during project execution: No wonder why their pivotal position helps the managers to establish a higher understanding with both contractor personnel and consultants. The lowest correlation of views between the contractor personnel and the consultants arise from the spot on difference between their workspace environments. Whereas the contractor personnel operate in the field, the consultants are mostly restricted to their design offices.
Keywords: Critical success factors; Construction projects; Civil Engineering (0543); Engineering (0537); Management (0454)